ANALISIS KEPUTUSAN PEMBELIAN DENGAN PERSEPSI SEBAGAI VARIABEL INTEVERNING PADA PRODUK DETERGEN MEREK SAYANG DI KOTA MOJOKERTO - Terry Terentya; Dhani Ichsanuddin Nur; Sugeng Purwanto (JURNAL ILMIAH EDUNOMIKA, 2023)
This research aims to determine the influence of brand image, product attributes, and perceptions on the purchase decision of Sayang brand detergent products in Mojokerto City. In this research, Sayang detergent is a newly launched brand by Kapal Api, which currently falls under the category of new products in the home care segment. This research was conducted on Sayang detergent consumers in Mojokerto City. The sample size in this research was 100 people using purposive sampling technique. The type of data used was quantitative data. The data collection technique used in this research involved the use of questionnaires, journals, as well as secondary data taken from the sales data of Sayang detergent in Mojokerto City. Smart PLS analysis was employed for data analysis in this research. The conclusion of this research indicates that brand image, product attributes, through perception, have an influence on the purchase decision of Sayang detergent. As a new brand, Sayang detergent has established a positive brand image, attributes, and consumer perceptions. However, this aspect should be continuously monitored to ensure the ability to compete and improve the sales figures of Sayang detergent.